2020
DOI: 10.1016/j.jacbts.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Antagonism of Hypoxia-Inducible Factor Isoforms in Cardiac, Vascular, and Renal Disorders

Abstract: Highlights HIF-1α and HIF-2α promote cellular adaptation to acute hypoxia, but during prolonged activation, these isoforms exert mutually antagonistic effects on the redox state and on proinflammatory pathways. Imbalances in HIF-1α and HIF-2α may contribute to the evolution and progression of chronic cardiac, vascular, and renal disorders. Selective activation of HIF-2α can be achieved with drugs that inhibit isoform-selective PHDs or that promote the redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 104 publications
0
62
0
1
Order By: Relevance
“…These authors also proposed several SGLT2-associated renal mechanisms that included increased β-hydroxybutyrate levels and expression of hypoxia-inducible factors (HIFs) [ 34 ]. Furthermore, the increase in erythropoiesis may be explained by SGLT2 inhibitor-mediated activation of sirtuin-1 signaling and subsequent regulation of imbalances in HIF-1α and HIF-2α [ 35 ]. Taken together these findings indicate that increased erythropoiesis associated with SGLT2 inhibition appears to reflect favorable intra-renal responses, rather than simple hemoconcentration through loss of intravascular fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also proposed several SGLT2-associated renal mechanisms that included increased β-hydroxybutyrate levels and expression of hypoxia-inducible factors (HIFs) [ 34 ]. Furthermore, the increase in erythropoiesis may be explained by SGLT2 inhibitor-mediated activation of sirtuin-1 signaling and subsequent regulation of imbalances in HIF-1α and HIF-2α [ 35 ]. Taken together these findings indicate that increased erythropoiesis associated with SGLT2 inhibition appears to reflect favorable intra-renal responses, rather than simple hemoconcentration through loss of intravascular fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…Roxadustat, a new drug designed for renal anemia ( Chen et al, 2019b ), has been shown to inhibit hypoxia-inducible factor (HIF) and alleviate the progression of renal fibrosis ( Packer, 2020 ). Li et al (2020b) have implemented animal research to figure out that Roxadustat may retard the progression of fibrosis by regulating Akt/GSK-3β-dependent Nrf2 activation.…”
Section: New Therapies For Renal Fibrosismentioning
confidence: 99%
“…After years of investigation into the molecular pathophysiology of cardiac fibrosis in patients and experimental animals, it has been found that the mice subjected to TAC‐induced pressure overload manifest rapid cardiac decompensation with excess cardiac fibrosis and increased myocardial hypoxia 16 . HIF‐1α, which is essential for maintaining O 2 homeostasis, is activated in response to increased oxygen demand and relative hypoxia during pressure overload‐induced myocardial hypertrophy and fibrosis 21 . Therefore, the TAC model, which includes chronic ischemia and/or hypoxia has been identified as one of the most suitable models for hypoxia‐induced myocardial fibrosis 9,17 .…”
Section: Discussionmentioning
confidence: 99%